Bethabara Moravian Church, showing Dr. Kalberlahn's laboratory behind the church. - (:unkn) unknown (Forsyth County Public Library, 2010)
Photo made in the 1960s.
Bethabara Moravian Church, showing Dr. Kalberlahn's laboratory behind the church. The laboratory was "arranged" in 1757 and completed about 1759. At the left, toward the church, are the foundation stones of the apothecary shop, built in 1763.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth